The Development of Microscopic Imaging Technology and its Application in Micro- and Nanotechnology - Wang, Yong; Zhang, Xiushuo; Xu, Jing; Sun, Xiangyu; Zhao, Xiaolong; Li, Hongsheng; Liu, Yanping; Tian, Jingjing; Hao, Xiaorui; Kong, Xiaofei; Wang, Zhiwei; Yang, Jie; et al. (Frontiers in Chemistry, 2022)
As a typical microscopic imaging technology, the emergence of the microscope has accelerated the pace of human exploration of the micro world. With the development of science and technology, microscopes have developed from the optical microscopes at the time of their invention to electron microscopes and even atomic force microscopes. The resolution has steadily improved, allowing humans to expand the field of research from the initial animal and plant tissues to microorganisms such as bacteria, and even down to the nanolevel. The microscope is now widely used in life science, material science, geological research, and other fields. It can be said that the development of microscopes also promotes the development of micro- and nanotechnology. It is foreseeable that microscopes will play a significant part in the exploration of the microworld for a long time to come. The development of microscope technology is the focus of this study, which summarized the properties of numerous microscopes and discussed their applications in micro and nanotechnology. At the same time, the application of microscopic imaging technology in micro- and nanofields was investigated based on the properties of various microscopes.